Analisis Pengaruh Bauran Pemasaran Terhadap Rumah Sakit Publik dan Privat: Systematic Review - Edithia, Tiara; Ditya, Tantri Puspa; Puspita, Dewi Citra (UI Scholars Hub, 2020)
The types of healthcare services available to patients in general may be divided into two categories – public and private hospitals. Mix-marketing element is a marketing approach that may be used to evaluate factors that affect patient tendency to choose one type of healthcare service. Aims: identify factors that affect patient tendency to choose public and private hospitals. This study implemented the Preferred report items for systematic reviews and meta-analysis (PRISMA) method. Literature search in PubMed and Google Scholar using the keywords mix-marketing element, private hospital, and public hospital resulted in six studies that use the mix-marketing element with a combination of the 7 P factors (7P), including Product, Price, Promotion, Place, People, Process, and Physical Evidence. One research found two categories of factors patient tendency to choose a hospital, including People and Product. Meanwhile, the second study showed the relationship between price and physical evidence with the tendency to choose public hospitals, whereas the tendency to choose private hospital is affected by product, place, promotion, and personnel. In general, the elements people, process, and healthcare services from the mix-marketing method affects patient tendency to choose both, public and private hospitals, though all seven factors in the mix-marketing method showed to influence the tendency to choose public and private hospitals.